Contractual Arrangements in Philippine Fisheries - Gideon P. Carnaje (Philippine Institute for Development Studies (PIDS), 2007)
Economists have begun the quest for explanations of contractual choices in developing countries and especially for pervasiveness of informal credit and insurance arrangements and interlinkages observed in agricultural and fishing contracts. In the case of fisheries, what is needed is an in-depth knowledge of real world contract provisions and categorization of contractual arrangements to guide analysis of contractual arrangements. This paper is a modest contribution toward this particular end. The present study also draws upon modern contract theory to explain the existence of a variety of contractual arrangements in aquaculture and marine fishing. Certain regularities to be found within the fishing economies of the Philippines include share contracts between aquaculture owner-operators and tenant/laborers and between boat owners and crew members as well as interlinkage of credit, labor, and marketing relations. Future work would entail understanding the fundamental incentives underlying contractual arrangements in fisheries that will allow one to evaluate the efficiency and equity implications of contract use and will aid in predicting their influence in the distribution of returns as their usage in the fishery sector increases.
Keywords: 330; agricultural contracts; contractual arrangements; fishing contracts; fishery sector; informal credit; Vertragsanbau; Fischerei; Philippinen